(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
The current study aimed to uncover the influence relationship between the independent variable (emotional contagion) and the dependent variable (team effectiveness). This was achieved by understanding the conceptual framework of these variables and determining their level of availability at Al-Furat Al-Awsat Hospital. This was done based on the theory of emotional contagion and the team effectiveness model to explain the relationship between these variables. The research problem was represented by the need to understand the extent to which the spread of positive and negative emotions, represented by the dimensions of emotional contagion (sadness, happiness, anger, love, fear), affects the overall performance of work teams, their effectiveness, and the achievement of their goals. Although previous research has addressed this topic, most of it focused on Western work environments or neglected to study the integrated impact of all dimensions of emotional contagion on team effectiveness, creating a research gap that this study sought to fill. The descriptive analytical approach was adopted as the basic research methodology by describing the intellectual contents of the research variables. The questionnaire was used as the main tool for data collection. A sample of medical and administrative cadres in the hospital was selected as the research sample. The total sample size was (223) individuals. Their data were collected through two methods: the first was by distributing the questionnaire electronically to (122) individuals, and the second was by distributing it manually to (101) hospital workers. Both (Excel) and (JASP v.19) programs were adopted in the statistical analysis. The results indicated the acceptance of the first main hypothesis, which states that there is a statistically significant effect of emotional contagion at the overall level on the effectiveness of work teams. The results also showed the acceptance of the second main hypothesis at the level of the dimensions of emotional contagion, as the effect of the two dimensions (sadness and anger) was negative, while the dimensions of happiness, love and fear had a positive effect on the effectiveness of work teams